Strategi Positioning dan Branding Destinasi Pariwisata Manggarai Timur Dalam Mendukung Citra New Tourism Territory (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Studies on positioning and branding strategies for East Manggarai Tourism Destinations are currently very limited. Previous studies were conducted only partially and focused only on tourist attractions. On the other hand, the high gap between domestic and foreign tourist visits is nearly 10.000 times. Foreign tourist visits have not yet reached a significant number. However, East Manggarai has tremendous tourism potential with 118 tourist attractions spread across four strategic tourism areas in the region. Therefore, this study aims to analyze the positioning and branding strategies of East Manggarai Tourism Destinations by mapping tourism market segmentation trends. Designed with a quantitative descriptive approach, questionnaires were distributed to tourists accidentally encountered in the field. The branding formulation "Keep Exploring The Dangerous Golden Dragon in the World" is expected to strengthen the image of East Manggarai Tourism Destinations as a competitive new brand and supports the image of tourism in East Nusa Tenggara as The New Tourism Territory.